The scourge of green monetarism - Sawyer, Malcolm (Brazilian Keynesian Review, 2015)
The idea of full reserve banking (under various names) has been adopted by parts of the green and ecological movements (e.g. Green Party of England and Wales). The paper argues that full reserve banking (FRB) would represent a ‘green monetarism’. As with monetarism, FRB would focus on inflation and its control through the money supply. FRB would face problems with the control of the effective money supply as other means of payment developed. Its major problem would though come from the connection which would be established between the budget deficit and changes in the money supply. Fiscal policy would become completely subordinated to the control of the money supply. There is no reason to think that it would enable fiscal policy to be set in a manner conducive to high levels of employment, and at times would lead to substantial unemployment, and at others to ‘overheating’ of the economy. Through denying fiscal policy’s role as an ‘automatic stabiliser’, full reserve banking would be a force for instabilities.